Frank W. Carpenter papers - Carpenter, Frank W. (Frank Watson), 1871-1938.
Correspondence, memoranda, newspaper clippings, printed material, and other papers concerning Carpenter's service as governor of Moro Province and as director of the Bureau of Non-Christian Tribes in the Philippines (1899-1922). Also relates to his attempts as a resident of the United States Soldiers' Home to secure legislation for veterans' medical care (1935-1937). Correspondents include W. Cameron Forbes, James G. Harbord, Francis Burton Harrison, Frank Ross McCoy, Manuel Luis Quezon, Richard B. Wigglesworth, and Leonard Wood.
U.S. public official and veterans' advocate.
Collection material in English.
Keywords: Forbes, W. Cameron -- 1870-1959 -- Correspondence; Harbord, James G. -- 1866-1947 -- Correspondence; Harrison, Francis Burton, -- 1873-1957 -- Correspondence; McCoy, Frank Ross, -- 1874-1954 -- Correspondence; Quezon, Manuel Luis, -- 1878-1944 -- Correspondence; Wigglesworth, Richard B. -- 1891-1960 -- Correspondence; Wood, Leonard, -- 1860-1927 -- Correspondence; Philippines. -- Bureau of Non-Christian Tribes; United States Soldiers' Home; Governors -- Philippines -- Moro Province; Veterans -- Medical care -- Law and legislation -- United States; Philippines -- Politics and government -- 1898-1935.; Public officials